Fate of transition metals during passive carbonation of ultramafic mine tailings via air capture with potential for metal resource recovery. (April 2018) - Hamilton, Jessica L.; Wilson, Siobhan A.; Morgan, Bree; Turvey, Connor C.; Paterson, David J.; Jowitt, Simon M.; McCutcheon, Jenine; Southam, Gordon
Graphical abstract: Highlights: Trace metals (Fe, Mn, Cr, Ni, Co) released by ultramafic mineral weathering are sequestered within Mg-carbonate cements. Trace metals are immobilised both by incorporationinto hydromagnesite and by physical trapping of metal rich grains. Fe, Ni, Co and Cr rich oxide and alloy mineralscould potentially be recovered from carbon mineralisation treatments. Abstract: Mineral carbonation in ultramafic mine tailings is generally accepted to be a safe and long term means of trapping and storing CO2 within the structures of minerals, but it poses the risk of releasing potentially hazardous metal contaminants from mineral wastes into the environment. Stockpiles of reactive, finely pulverised ultramafic mine tailings are ideal natural laboratories for the observation and promotion of the carbonation of Mg-silicate and Mg-hydroxide waste minerals via reaction with atmospheric or industrial CO2 . However, ultramafic mine tailings commonly contain first-row transition metals (e.g., Cr, Co, Cu, Ni) in potentially toxic concentrations within the crystal structures of Mg-silicates, sulphides, and oxides. These transition metals are likely to be mobilised by mineral carbonation reactions, which require mineral dissolution to supply cations for reaction with carbon. At Woodsreef Chrysotile Mine, New South Wales, Australia, transition metals (i.e., Fe, Cr, Ni, Mn, Co, Cu) are most concentrated within minor oxides (magnetite and chromite) and trace alloys (awaruite, Ni2-3 Fe and wairauite, CoFe) in serpentine tailings, however, mobilisation of transition metals appears to occur predominantly during dissolution of serpentine and brucite, which are more abundant and reactive phases, respectively. Here, we present new synchrotron X-ray fluorescence mapping data that provide insights into the mobility of first-row transition metals (Fe, Cr, Ni, Mn, Co, Cu) during weathering and carbonation of ultramafic mine tailings collected from the Woodsreef Chrysotile Mine. These data indicate that the recently precipitated carbonate minerals, hydromagnesite [Mg5 (CO3 )4 (OH)2 ·4H2 O] and pyroaurite [Mg6 Fe2 (CO3 )(OH)16 ·4H2 O] sequester trace metals from the tailings at concentrations of 10 s–100 s of ppm, most likely via substitution for Mg or Fe within their crystal structures, or by the physical trapping of small (μm-scale) transition-metal-rich grains (i.e., magnetite, chromite, awaruite), which are stabilised within alkaline carbonate cements. Trace transition metals are present at relatively high concentrations in the bulk tailings (i.e., ∼0.3 wt.% NiO and Cr2 O3 ) and they are largely retained within the unaltered mineral assemblage. The weathering products that occur at the surface of the tailings and form a cement between grains of partially dissolved gangue minerals immobilise transition metals on spatial scales of micrometres and at comparable concentrations to those observed in the unaltered tailings. The end result is that trace metals are not present at detectable levels within mine pit waters. Our observations of metal mobility during passive carbonation suggest that mineral products of accelerated carbonation treatments are likely to sequester trace metals. Thus, accelerated carbonation is unlikely to pose an environmental risk in the form of metalliferous drainage so long as the neutralisation potential of the tailings is not exceeded. Understanding both trace transition metal geochemistry and mineralogy within materials targeted for mineral carbonation could allow optimisation of treatment processes and design for recovery of valuable metals. In ex situ reactors employing acid pre-treatments, trace metals mobilised from reactive phases such as serpentine and brucite could potentially be recovered using pH-swing methods, while recalcitrant metal-rich accessory minerals, including magnetite, awaruite and chromite, could be recovered from treated residue material by conventional mineral separation processes. Recovery of valuable metals (i.e., Ni, Cr and Co) as by-products of accelerated mineral carbonation technologies could also provide an important economic incentive to support broader adoption of this technology.